Real-time wireless acquisition of process data - Ye Zhang (The Research Institute of the Finnish Economy (ETLA), 2011)
This study discusses a novel method called automatic process measurement, which is based on the idea of mining process data from workflow logs. We improve the process mining technique by using Bluetooth wireless technology to do real-time acquisition of process data. The automatic measurement system is capable of collecting process data of elderly people's daily process as well as nursing personnel's behavior in the open healthcare. Similarly, retail and logistics processes can be measured with the system. The data can be used further in process analysis and modeling.
Keywords: D22; C81; I11; 330; real-time data acquisition; automatic process measurement; process mining; Bluetooth; Data Mining; Prozessmanagement